2017
DOI: 10.1364/josab.34.0000d1
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous reflection of visible light by all-dielectric gradient metasurfaces

Abstract: Plane wave scattering by a planar metasurface composed of two periodically alternating rectangular dielectric rods is considered. A rigorous integral equation methodology is employed for the analysis and the accurate determination of the reflected and transmitted fields. Systematic optimizations with respect to the configuration's parameters are performed, which reveal that it is possible to obtain significantly enhanced anomalous reflection (with simultaneously suppressed ordinary reflection predicted by Snel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
1
22
0
3
Order By: Relevance
“…The latter implies also that the −1-order is reflected back in the same (second) quadrant of the plane with that where the incident field impinges on the metasurface, as well as to be transmitted back in the corresponding (third) quadrant [9]. The angle of incidence is fixed at θ = 60 o , since, as analyzed in [9], then the reflection angle (measured as the angle between the negative z-axis and the wavevector of the −1-reflected order) is close to the angle incidence θ.…”
Section: Numerical Results and Dis-cussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The latter implies also that the −1-order is reflected back in the same (second) quadrant of the plane with that where the incident field impinges on the metasurface, as well as to be transmitted back in the corresponding (third) quadrant [9]. The angle of incidence is fixed at θ = 60 o , since, as analyzed in [9], then the reflection angle (measured as the angle between the negative z-axis and the wavevector of the −1-reflected order) is close to the angle incidence θ.…”
Section: Numerical Results and Dis-cussionmentioning
confidence: 99%
“…The angle of incidence is fixed at θ = 60 o , since, as analyzed in [9], then the reflection angle (measured as the angle between the negative z-axis and the wavevector of the −1-reflected order) is close to the angle incidence θ. The propagation direction of the −1-transmission order is symmetric with respect to the z-axis to that of the −1-reflected order.…”
Section: Numerical Results and Dis-cussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [9] and [10], it was demonstrated that a gradient dielectric metasurface composed of two periodically alternating lossless materials can generate anomalous reflection phenomena in the visible frequency range; namely the power of the −1-reflected order is significantly enhanced while the corresponding powers of the 0-reflected and transmitted orders (dictated by Snell's law) are annihilated. The effective properties of the metasurface's unit cell offering these characteristics can be found in ordinary dielectrics.…”
Section: Introductionmentioning
confidence: 99%